Identification of blood source preferences and Leishmania infection in sand flies (Diptera: Psychodidae) in north-eastern Algeria - Messahel, Nacer Eddine; Benallal, Kamel Eddine; Halada, Petr; Lafri, Ismail; Manseur, Hemza; Hakem, Ahcene; Houali, Karim; Harrat, Zoubir; Volf, Petr; Dvorak, Vit (Veterinary parasitology, regional studies and reports, 2022)
Leishmaniases are among the most neglected vector-borne diseases, infecting humans as well various animal hosts with clinical outcomes varying from cutaneous disorders to visceral and life-threatening disease. In Algeria, canine leishmaniasis (CanL) caused by Leishmania infantum is endemic mainly throughout the northern regions of the country with the Mediterranean climate that favours the occurrence of Larroussius sand flies, the vectors of the parasite. This study conducted in Bougaa and Kherrata, two regions located in north-eastern Algeria and endemic for CanL, focuses on: i) composition of sand fly fauna, ii) screening of Leishmania parasites and iii) the blood sources of engorged females. Entomological surveys were conducted between June and September 2019 using CDC light-traps in rural areas of both regions. Sand fly specimens were morphologically identified, females were screened for Leishmania DNA using kDNA and ITS1 primers, blood meals in engorged females were identified by peptide mass mapping (PMM)-based MALDI-TOF mass spectrometry and confirmed by DNA sequencing analysis. Overall, 1940 specimens (844 males, 1096 females) were collected, all belonging to the subgenus Larroussius: Phlebotomus perniciosus, (94.64%), Ph. perfiliewi (4.74%) and Ph. longicuspis (0.62%). No Leishmania DNA was detected in the evaluated pools (n = 106) (1096 females). PMM-based MALDI-TOF MS successfully identified a source of blood in 92% (141/154) of engorged females (135 Ph. perniciosus and 6 Ph. perfiliewi). All blood meals were taken from domestic cattle (Bos taurus) except for one originating from a dog (Canis lupus familiaris) and one from sheep (Ovis aries). Sequencing of host cytochrome B gene confirmed these identifications but showed lower success rate of 58% (29/50), demonstrating the high effectivity of peptide mass mapping (PMM)-based MALDI-TOF mass spectrometry for routine identification of blood meals of varying degree of digestion. Our findings represent first record of cattle and dog blood in sand flies in Algeria and striking feeding preference of local sand fly population at domestic sites of studied regions for cattle which may play an important role in parasite transmission. Further studies are needed to better understand potential contribution of cattle to ecology of sand flies and epidemiology of leishmaniasis in north-eastern Algeria.
Keywords: Algeria; psi; Sheep; nemoci skotu; Dogs; Alžírsko; Sand flies; Phlebotomus; kinetoplastová DNA; Female; zvířata; MALDI-TOF MS; Blood meal; Sheep Diseases; Cattle; ženské pohlaví; leishmanióza; Cattle Diseases; Male; Phlebotomus perniciosus; nemoci psů; skot; Dog Diseases; Leishmaniasis; Leishmania; Leishmania infantum; Animals; mužské pohlaví; Psychodidae; nemoci ovcí; DNA, Kinetoplast; ovce